Profil Pasien Cedera Anterior Cruciate Ligament (ACL) yang Menjalani Rekonstruksi ACL di RSUP Prof. Dr. R. D. Kandou Manado - Rawung, Rangga B. V.; Meylia, Indah; Wagiu, Angelica M. J. (e-CliniC, 2024)
Abstract: Knee injuries are among the most common sports-related injuries experienced by athletes. One of the frequently encountered knee injury is anterior cruciate ligament (ACL) tear. This study aimed to obtain the profile of patients with ACL injuries whor underwent ACL reconstruction at Prof. Dr. R. D. Kandou Hospital, Manado. This was a descriptive study with a retrospective-prospective method, using secondary data. The results obtained 16 patients who met the inclusion criteria. The incidence of ACL injuries was the highest in males (81.25%) aged 17-25 years (68.75%). The most common cause of ACL injuries was sports activities (81.25%), and many patients were classified as having first-degree obesity (37.5%). ACL injuries often occurred with meniscal injuries (56.25%). The most commonly used graft was the Hamstring (semi T) graft (43.75%). Patients typically presented within 1-6 months of the injury onset (68.75%), and the majority of knee functional outcomes were categorized as moderate (43.75%). In conclusion,  anterior cruciate ligament injuries most often occur in men, aged 17-25 years. Sports activities and obesity are more at risk of ACL injury. Most ACL injuries are associated with meniscus injuries, and onsets of 1-6 months. The operative management graft that is often used is the Hamstring graft, with functional results in the middle category. Keywords: anterior cruciate ligament injury; reconstruction; graft operative management    Abstrak: Cedera lutut merupakan salah satu cedera olahraga yang paling banyak dialami oleh atlet; salah satunya yang sering dijumpai ialah robekan anterior cruciate ligament (ACL). Penelitian ini bertujuan untuk mengetahui profil pasien cedera ACL yang menjalani rekonstruksi ACL di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif dengan pendekatan retrospektif prospektif menggunakan data sekunder. Hasil penelitian mendapatkan 16 pasien yang memenuhi kriteria inklusi. Insiden cedera ACL paling banyak terjadi pada laki-laki (81,25%), kelompok usia 17-25 tahun (68,75%), penyebab cedera karena aktivitas olahraga (81,25%), dan pasien kategori obesitas derajat 1 (37,5%). ACL sering terjadi dengan adanya cedera meniskus (56,25%), graft yang paling sering digunakan yaitu graft Hamstring (semi T) (43,75%). Sebagian besar pasien datang dengan onset kejadian 1-6 bulan (68,75%) dengan hasil fungsional lutut kategori menengah (43,75%). Simpulan penelitian ini ialah cedera ACL sering terjadi pada laki-laki berusia 17-25 tahun. Aktivitas olahraga dan obesitas berisiko terjadinya cedera ACL. Mayoritas cedera ACL berhubungan dengan cedera meniskus, onset sebagian besar pasien cedera ACL ialah 1-6 bulan, penatalaksanaan operatif dengan graft Hamstring, dengan luaran hasil fungsional kategori sedang. Kata kunci: cedera anterior cruciate ligament; rekonstruksi; graft penatalaksanaan operatif